2016
DOI: 10.1016/j.jsb.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling HIV protease flaps dynamics by Constant pH Molecular Dynamics simulations

Abstract: a b s t r a c tThe active site of HIV protease (HIV-PR) is covered by two flaps. These flaps are known to be essential for the catalytic activity of the HIV-PR, but their exact conformations at the different stages of the enzymatic pathway remain subject to debate. Understanding the correct functional dynamics of the flaps might aid the development of new HIV-PR inhibitors. It is known that, the HIV-PR catalytic efficiency is pHdependent, likely due to the influence of processes such as charge transfer and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
2
11
0
Order By: Relevance
“… The data described here supports the research article “Unraveling HIV Protease Flaps Dynamics by Constant pH Molecular Dynamics Simulations” (Soares et al, 2016) [1] . The data involves both standard Molecular Dynamics (MD) and Constant pH Molecular Dynamics (CpHMD) to elucidate the effect of protonation states of catalytic dyad on the HIV-PR conformation.…”
supporting
confidence: 87%
See 1 more Smart Citation
“… The data described here supports the research article “Unraveling HIV Protease Flaps Dynamics by Constant pH Molecular Dynamics Simulations” (Soares et al, 2016) [1] . The data involves both standard Molecular Dynamics (MD) and Constant pH Molecular Dynamics (CpHMD) to elucidate the effect of protonation states of catalytic dyad on the HIV-PR conformation.…”
supporting
confidence: 87%
“…The crystal structure 2HB4 was used as apo form of HIV-PR [8] . Before starting the simulation on the 1KJF structure, we performed the mutation N25D [1] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Equilibrium MD simulations of IUS for 1 µs showed large conformational fluctuation of the flap region (Figure S14), although no distinct conformational transitions to the open or semi-open conformations observed by an X-ray crystallographic measurement and previous MD simulations [56,[92][93][94] were found during the simulation time, which may be a source of the slight overestimation of the increase of . We also performed the alchemical FEP calculations for IUS with different protonation states of the carboxylic acids of Asp25, i.e., the mono-protonated state and the di-protonated state, for comparison, and found that the difference in the protonation state moderately altered the free energy change upon the mutation by ~1 kcal/mol (Table S6).…”
Section: Qm Region Includesmentioning
confidence: 84%
“…X-ray crystallographic studies reported conformational changes of the protein upon mutations [13,19,20,94]. X-ray crystallographic structures of HIV-1 protease binding Indinavir exhibit large conformational changes of 80s loop comprised of amino acids 79-83 and the pyridyl group of Indinavir upon nine mutations including V82T [20] and two mutations including V82A [21],…”
Section: Qm Region Includesmentioning
confidence: 99%
“…Equilibrium MD simulations of IUS for 1 µs showed large conformational fluctuation of the flap region (Figure S12), although no distinct conformational transitions to the open or semi-open conformations observed by an X-ray crystallographic measurement and previous MD simulations [86][87][88] were found during the simulation time, which may be a source of the slight overestimation of the increase of . We also performed the alchemical FEP calculations for IUS with different protonation states of the carboxylic acids of Asp25, i.e., the mono-protonated state and the di-protonated state, for comparison, and found that the difference in the protonation state moderately altered the free energy change upon the mutation by ~1 kcal/mol (Table S6).…”
Section: Dementioning
confidence: 88%